Predictor Factors of Atherosclerosis and Atherosclerosis Plaque in Rheumatoid Arthritis Patients - Pambudi, Joko Rilo; Isbagio, Harry; Mulyadi, Rahmad; Abdullah, Murdani (Indonesian Journal of Rheumatology, 2016)
Background: Atherosclerosis and cardiovascular diseases have been known as the cause of increasing mortality among rheumatoid arthritis (RA) patients. Carotid intima media thickness (CIMT) measurement by ultrasound has been used as surrogate marker of atherosclerosis and cardiovascular disease.Methods: A cross sectional study of 86 RA patients fulfills EULAR/ACR 2010 critera for RA was conducted to study proportion and predictor factors of atherosclerosis and atherosclerosis plaque in rheumatoid arthritis patients.Results: Atherosclerosis and plaque was found in 47,7% and 29 % of patients. Age â¥ 40 yo, hypertension and duration of illness â¥ 24 mo were associated with atherosclerosis in multivariate logistic regression analysis with OR 10.70 (95% CI: 2.93-39.10), 4.99 (95% CI: 1.15-21.61) and 3.66 (95% CI: 1.11-11.99) respectively. Whereas hypertension, presence of antiCCP antibody and age â¥ 40 yo, were associated with plaque formation with OR 3.96 (95% CI: 1.15-13.57), 3.20 (95% CI: 1.11-9.24) and 3.61 (95% CI: 1.03-12.63) respectively.Conclusions: Age â¥ 40 yo, hypertension and duration of illness â¥ 24 mo was the predictors ofatherosclerosis, while hypertension, presence of antiCCP antibody and age â¥ 40 yo was the predictors of atherosclerosis plaque.Key words: atherosclerosis, intima media thickness, predictor, rheumatoid arthritis, ultrasonography.